A systematic review of reasons for gatekeeping in palliative care research. (June 2016) - Kars, Marijke C; van Thiel, Ghislaine JMW; van der Graaf, Rieke; Moors, Marleen; de Graeff , Alexander; van Delden, Johannes JM
Background: When healthcare professionals or other involved parties prevent eligible patients from entering a trial as a research subject, they are gatekeeping . This phenomenon is a persistent problem in palliative care research and thought to be responsible for the failure of many studies. Aim: To identify potential gatekeepers and explore their reasons for gatekeeping in palliative care research. Design: A 'Review of Reasons' based on the systematic Preferred Reporting Items for Systematic Reviews and Meta-Analyses approach and a thematic synthesis. Data source: PubMed, Embase, Cumulative Index to Nursing and Allied Health Literature and PsycINFO from 2000 to May 20 2015 were searched. Studies in children (aged <18 years) and patients with dementia were excluded. Results: Thirty papers on gatekeeping in palliative care research were included. Five groups of potential gatekeepers were identified: healthcare professionals, research ethics committees, management, relatives and researchers. The fear of burdening vulnerable patients was the most reported reason for gatekeeping. Other reasons included 'difficulty with disclosure of health status', 'fear of burdening the patient's relatives', 'doubts about the importance or quality of the study', 'reticent attitude towards research and (research) expertise' and 'logistics'. In hospice and homecare settings, the pursuit of comfort care may trigger a protective attitude. Gatekeeping is also rooted in a (perceived) lack of skills to recruit patients with advanced illness. Conclusion: Gatekeeping is motivated by the general assumption of vulnerability of patients, coupled with an emphasis on the duty to protect patients. Research is easily perceived as a threat to patient well-being, and the benefits appear to be overlooked. The patients' perspective concerning study participation is needed to gain a full understanding and to address gatekeeping in palliative care research.